2020
DOI: 10.1097/mlr.0000000000001369
|View full text |Cite
|
Sign up to set email alerts
|

Medication Use and Health Care Utilization After a Cost-sharing Increase in Schizophrenia

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…It should also be noted that the group of respondents with eligibility is more heterogeneous than the diabetes group; thus, focusing on another high-risk patient group might have revealed further differences across years. For example, patients with severe mental health disorders also seem at high risk based on previous evidence [ 15 , 42 ]. However, this patient group was small and was largely undetectable in our survey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that the group of respondents with eligibility is more heterogeneous than the diabetes group; thus, focusing on another high-risk patient group might have revealed further differences across years. For example, patients with severe mental health disorders also seem at high risk based on previous evidence [ 15 , 42 ]. However, this patient group was small and was largely undetectable in our survey.…”
Section: Discussionmentioning
confidence: 99%
“…In Finland, an increase in medication co-payments has been a recurrent policy used to create savings. Recent studies applying quasi-experimental analytical strategies have shown coinciding negative effects: decreases in the purchasing of medications among patients with schizophrenia and stagnation in the preceding decreasing trend in psychiatric hospitalisations [ 15 ]; decreases in the consumption of type 2 diabetes medications and worsening glycaemic control [ 16 ], and increases in the use of last-resort social assistance vouchers to pay for type 2 diabetes medications [ 17 ]. In longitudinal studies using survey data, increases in financial problems in buying medications and dissatisfaction among people with type 2 diabetes have been observed [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decades however, medicine co-payment increases have been common also in European countries [ 44 , 45 ]. A Finnish study showed reduction in medicine use among persons with schizophrenia after a medicine co-payment increase, coinciding a halt in the preceding decreasing trend in psychiatric hospitalizations, but with no other significant differences in health care utilization [ 46 ]. A Spanish study showed marked decreases in consumption after institution of small copayment for medicines among older age groups whom previously were completely exempt [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Larger inconsistencies are found among mental health patients, [13][14][15] for whom critical economic assumptions, such as individual rationality are not met, 16 and an increase in patient cost-sharing seems to be associated with poorer medication adherence and outcomes. [17][18][19] Additionally, relative price changes (i.e., from 10 to 20%) are known to produce smaller consumption reductions than free-to-fee increases (i.e., 0 to 10%). 20 We explored these questions with a quasi-experimental design by taking advantage of a natural experiment in Spain.…”
mentioning
confidence: 99%
“… 11 , 12 Larger inconsistencies are found among mental health patients, 13 , 14 , 15 for whom critical economic assumptions, such as individual rationality are not met, 16 and an increase in patient cost‐sharing seems to be associated with poorer medication adherence and outcomes. 17 , 18 , 19 Additionally, relative price changes (i.e., from 10 to 20%) are known to produce smaller consumption reductions than free‐to‐fee increases (i.e., 0 to 10%). 20 …”
mentioning
confidence: 99%